6B.07: HYPERTENSIVE PATIENTS EXHIBIT GUT MICROBIAL DYSBIOSIS AND AN INCREASE IN TH17 CELLS. (June 2015) - Kim, S.; Rodriguez, V.; Santisteban, M.; Yang, T.; Qi, Y.; Raizada, M.; Pepine, C.
Abstract : Objective: Hypertension (HTN) is a most prevalent risk factor associated with diabetes, obesity, metabolic syndrome and cardiovascular disease, all of which have been recently associated with gut microbial dysbiosis. However, a relationship between gut microbiota and HTN has not been studied. Thus, the objective of our study was to investigate if gut dysbiosis is present in hypertensive patients. Design and method: We conducted a pilot study using fecal and blood samples obtained from hypertensive (n = 7, systolic BP > 125 mmHg) and normotensive (n = 13, systolic BP < 125 mmHg) patients. Samples were analyzed for Chao richness, Shannon diversity and Pielou evenness using 16 s rRNA sequencing to determine microbiome composition. FACS analysis was used to examine changes in the inflammatory cells levels in these patients. Results: We observed marked decreases in microbial richness and diversity in the HTN patients (Figure 1). In addition, this group also showed a trend towards a decrease in evenness in species from certain genus such as bacteriodetes. Furthermore, increases in myeloid inflammatory cells (94% increase in CD14+ cells, 200% increase in CD11b+ cells) and Th17 cells (700% increase in CD4+ IL17+ cells) were observed in HTN patients compared to normotensives (Figure 2). An increase in the Th17 cells is extremely relevant finding since levels of these cells are regulated by gut-intrinsic mechanisms that generate pro-inflammatory cytokines such as TGF-β1, TNF-α, IL-1β and IL-6. Conclusions: Taken together, these observations suggest that gut microbial dysbiosis plays a key role in HTN and the establishment of a systemic proinflammatory status through regulation of Th17 cell levels. Thus, restoring the gut microbial balance could be a novel therapeutic strategy for the treatment of HTN. Figure. No caption available.